Εφαρμογή λιτών διεργασιών σε τερματικούς σταθμούς εμπορευματοκιβωτίων - Μοσχάκη, Ελένη (2021)
Purpose – The purpose of this paper is to present the key findings of a systematic literature review (SLR) on Lean for services at container terminals. Design/methodology/approach – The authors have utilised an SLR methodology proposed by Denyer and Tranfield (2009). A total of 20 papers have been systematically reviewed for evaluating and establishing the current status of Lean at container terminals. Findings – In general, the literature which concerns the implementation of lean philosophies at container terminals is quite limited and it is also considered urgent the conduction of additional research for the supplementation of the literature. According to the selected literature, the adoption of lean philosophies at container port terminals will enhance the services provided and the processes located at container terminals. The ultimate goal is the added value on services, for the client and the organization. Further attention is needed in the choice of those departments of port operations that the implementation of lean philosophies will be effective. Nevertheless, the port operators are facing many challenges concerning the implementation and integration of lean philosophies, that need to overcome. Research limitations/implications – This paper seeks to contribute to and broaden the limited body of evidence of the applicability of lean philosophies at container terminals and identify areas for further research and review. Originality/value – This paper makes an attempt to demonstrate the use of lean thinking for service industries and, in particular, container terminals. Through the systematic literature review, a limited number of papers on the use of lean philosophies at container terminals has been identified and this paper sets the foundation for future research on the use of process excellence methodologies such as lean.